ChemInform Abstract: A New Class of Homogeneous Visible‐Light Photocatalysts: Molecular Cerium Vanadium Oxide Clusters. Issue 48 (2nd December 2014) - Seliverstov, Andrey; Streb, Carsten
Abstract The structures of compounds (III) and (VI) are determined by single crystal XRD.